Red dawn - Feitshans, Buzz; Beckerman, Barry 1942-1996; Milius, John 1944-; Swayze, Patrick 1952-2009; Howell, C. Thomas 1966-; Thompson, Lea 1961- (Twentieth Century Fox Home Entertainment, 1984)
When Communist paratroopers descend on a high school football field in Colorado, a group of the school's students wages an all-out guerrilla war to save their town and their country
Keywords: World War III / Drama; Teenagers / United States / Drama; World War III / Underground movements / Drama; Guerrillas / United States / Drama; Civil defense / United States / Drama; Guerrillas -- United States -- Drama.; Civil defense -- United States -- Drama.; High school students -- Drama.; War films.; Action and adventure films.; Film remakes.; Feature films.; Remake; Abenteuerfilm; Guerilla; Kriegsfilm; High school; Schüler; Bürgerwehr; Soviet Union / Armed Forces / Parachute troops / Drama; Sowjetunion; USA; DVD-Video